The Influence of Alkaline Treatment of Recycled Natural Materials on the Properties of Epoxy Resin Composites - Kamal, Hamza M.; Kadhim, Mohammed J.; Mohammed, Raeid K. (Al-Khwarizmi Engineering Journal, 2018)
Natural fibers and particles reinforced composites are being broadly used due to their bio and specific properties such as low density and easy to machine and production with low cost. In this work, water absorption and mechanical properties such as tensile strength, flexural strength and impact strength of recycled jute fibers reinforced epoxy resin were enhanced by treating these fibers with alkaline solution. The recycled jute fibers were treated with different concentration of (NaOH) solution at (25 0C) for a period of (24) hours. From the obtained results, it was found that all these properties are improved when fibers treated with (7.5wt% NaOH) related to untreated fibers. Conversely, the mentioned properties of composites decreased after fibers treated with (10wt% NaOH). In addition, the hybrid composite with recycled jute fibers and recycled walnut shell powder showed obvious enhancement in the above-mentioned properties.